2020
DOI: 10.1186/s40249-020-00773-5
|View full text |Cite
|
Sign up to set email alerts
|

Malaria epidemiology and stratification of incidence in the malaria elimination setting in Harari Region, Eastern Ethiopia

Abstract: Background Ethiopia has shown notable progress in reducing the burden of malaria over the past two decades. Because of this progress, the country has shifted efforts from control to elimination of malaria. This study was conducted to analyse the malaria epidemiology and stratification of incidence in the malaria elimination setting in eastern Ethiopia. Methods A retrospective study was conducted to analyse the epidemiology of malaria by reviewing the district health office data from 2013 to 2019 in Harari Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 14 publications
8
29
3
Order By: Relevance
“…In spite of that, the peak in malaria cases occurred in July followed by November which is harvesting season during and after the main rainfall. The highest cases of malaria were detected during autumn (September-November) which was in consistent with the ndings of the studies carried out in Dembia [6], Dembecha [17], Northwest Tigray [4], Ataye [25], Guba [11], Jimma [41], and Harari [20]. It might be due to the heavy rains creating suitable environment for the breading of Anopheles mosquitoes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In spite of that, the peak in malaria cases occurred in July followed by November which is harvesting season during and after the main rainfall. The highest cases of malaria were detected during autumn (September-November) which was in consistent with the ndings of the studies carried out in Dembia [6], Dembecha [17], Northwest Tigray [4], Ataye [25], Guba [11], Jimma [41], and Harari [20]. It might be due to the heavy rains creating suitable environment for the breading of Anopheles mosquitoes.…”
Section: Discussionsupporting
confidence: 87%
“…The current study found that the total number of microscopically con rmed malaria cases were 793 with a proportion rate of 4.2%. It was markedly lower than previous studies conducted out of Ethiopia elsewhere (25.9%-30.3%) [15,16], and in several parts of the country such as in Dembia (21.8%) [6], Dembecha (16.34%) [17], Guba (51.04%) [11], Sibu Sire (20.07%) [18], Arjo-Didessa sugar development site (33.4%) [19], Harari (46.9%) [20], Chalia district (7.55%) [21], Abeshge (33.8%) [22], and Bale Zone (66.7%) [23]. The overall prevalence of the current study was also relatively lower than the ndings from other parts of Ethiopia like Northwest Tigray (6.96%) [4], Wereta (5.4%) [24], Kombolcha (7.52%) [9], Ataye (8.4%) [25], Halaba (9.5%) [5], Wolkite (8.56%) [26] and Arsi Negelle (11.45%) [27].…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that travelers or returning travelers from Ethiopia have also contributed to imported malaria cases in Qatar [ 25 ] and Kuwait [ 26 , 43 , 45 ]. Although the number of total malaria cases in Ethiopia is still very high, the country has shown notable progress in reducing the burden of malaria over the past two decades and this has shifted efforts from control to elimination of malaria in some regions of the country such as the Harari Region in Eastern Ethiopia [ 69 ]. The data showed that malaria incidence in the Harari Region declined from 42.9 cases per 1000 population in 2013 to only 6.7 cases per 1000 population in 2019 and malaria-related deaths decreased from 4.7 deaths per 1,000,000 population annually in 2013 to zero in 2015.…”
Section: Epidemiological Data From Countries Of Origin For Importementioning
confidence: 99%
“…The data showed that malaria incidence in the Harari Region declined from 42.9 cases per 1000 population in 2013 to only 6.7 cases per 1000 population in 2019 and malaria-related deaths decreased from 4.7 deaths per 1,000,000 population annually in 2013 to zero in 2015. Also, P. falciparum, P. vivax and mixed infections accounted for 69.2%, 30.6%, and 0.2% of the cases, respectively [ 69 ]. Ethiopia has set a goal to eliminate malaria by 2030 and artemether-lumefantrine treatment is being used as one of the cornerstone strategies for uncomplicated P. falciparum malaria [ 70 ].…”
Section: Epidemiological Data From Countries Of Origin For Importementioning
confidence: 99%
“…In 2018, 93% of malaria cases and 94% of malaria-related deaths were from sub-Saharan African countries [ 2 ]. In Ethiopia, malaria is the leading vector-borne disease, and the population living in malaria risk areas is still suffering from it [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%